Konsep Akad ' Seadanya ' dalam Sistem Perdagangan Masyarakat Banjar Kalimantan Selatan - Badrian; Muhammad Rizali; Pati Matu Zahra; Fithriana Syarqawie; Anwar Hafidzi; Khairatun Hisanah Alpasa (Al-Ujrah | Jurnal Ekonomi Syariah, 2023)
This journal examines the customary practices of the Banjar community in conducting "sighat akad" (contractual declaration) during transactions, which involve not only using the phrase "sell" or stating the price of the item as "I sell this shirt for fifty thousand,"but also adding the phrase "sell as is". The purpose of this research is to understand the perspective of the Shafi'i school of thought regarding the legal status of the contract of sale using the phrase "sell as is" in the Banjar community's practices. The research methodology employed in this study is field research with descriptive analysis, where data is collected through interviews and literary sources regarding the contractual agreements of buying and selling, which are then compared with the theories from the Shafi'i perspective. Based on the findings of this research, it can be concluded that according to the Shafi'i school of thought, the contract of sale using the phrase "sell as is" is permissible due to the mutual agreement between the seller and the buyer. This perspective aligns with the main objectives of a contract, which include the presence of mutual agreement, clarity of the object and terms, rightful ownership, and immediate payment and delivery.